Dermatological findings of vitamin B12 deficiency and resolving time of these symptoms - KOÇ, AHMET (TAYLOR & FRANCIS LTD, 2014)
Aim: The mucocutaneous changes observed during vitamin B12 deficiency in children have been published only as case studies and small case series. In this study, we aimed to demonstrate the frequency of mucocutaneous changes (particularly hyperpigmentation) seen during vitamin B12 deficiency and resolving time of these symptoms with vitamin B12 treatment. Material and methods: This prospective study was conducted at the pediatrics outpatient clinic of Harran and Yuzuncu Yil University Faculty of Medicine, among 57 patients, aged between 6 and 24 months, who were diagnosed with vitamin B12 deficiency following various examinations and tests. A detailed examination was performed in respect to skin and mucosal findings. Patients with vitamin B12 deficiency were administered intramuscular cyanocobalamin. Prospective examination was continued, and resolving time of symptoms after treatment was recorded. Results: The mean age of the patients enrolled in the study was found to be 12.75 +/- 4.75. Hyperpigmentation was reported in 49 (85.96%) patients enrolled in the study; atrophic glossitis in 40 (70.17%), brittle and matt hair in 13 (22.80%), skin lesions (particularly diaper dermatitis) in eight (15.78%) and cheilosis in four (7.01%) patients. Three months after the treatment initiation, hyperpigmentation improved in 87.75%, atrophic glossitis in 97.5% and brittle and matt hair in 92.3% of the patients. Five patients (8.77%) with continuing pigmentation by the end of sixth months were considered as nonresponsive to the treatment. Conclusion: Deficiency of vitamin B12 should be considered in the differential diagnosis of infants who present with skin and mucosal lesions.
Keywords: Hyperpigmentation; skin lesions; vitamin B12 deficiency; CLINICAL-MANIFESTATIONS; WHITE HAIR; HYPERPIGMENTATION; SKIN; LESIONS; MOUTH; GLOSSITIS; NAILS